THE IMPLEMENTATION OF ENGLISH LANGUAGE TUTORING "ENGLISH IS EASY" AND CHEAP " :Activity as a Method to Improved English Language Skill of Children and Adolescents at Makassar City - Musdalifah Ifah Rahman; Ilham Assidiq; Ismail Ismail; Elihami Elihami (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2020)
The community service activity (PKM) about English language tutoring with principle "English is Easy and Cheap" which was done by the writer given a brief description of the process of English language tutoring with used principle "English is Easy and Cheap". In this community service activity (PKM), English language became as a field of science that would be devoted or studied. Children and adolescents who came from poor parents' economy were the second material to be devoted or studied in this community service activity (PKM) about English language tutoring with used principle "English is Easy and Cheap". Some purposes or functions of this community service activity (PKM) that was in accordance with used the principles "English is easy and cheap" namely: the first purposed or function, to show the world, especially to wider community, especially children and adolescents that English was not difficult, and not scary like a monster. The second purposed or function that was to help children and adolescents who come from poor parents' economy to learn English language without collecting fees and help prepare themselves to carry out programs "AFTA" was a program that provided great opportunities for all Indonesian citizens to work and studied with mature English readiness. Keywords: English Language Tutoring, Children, Adolescents.